INTERNATIONAL PRACTICE OF ABATACEPT USE IN TREATMENT OF REFRACTORY UVEITIS IN PATIENTS WITH IDIOPATHIC JUVENILE ARTHRITIS - R.V. Denisova; E.I. Alexeeva (Вопросы современной педиатрии, 2011)
The article contains analysis of international practice of abatacept use in treatment of refractory uveitis in patients with idiopathic juvenile rheumatoid arthritis. Efficacy of T-cell co-stimulation blockade in treatment of severe autoimmune fontal uveitis has been proven on the models. Described clinical cases show that, abatacept is an effective and well tolerated biological drug, that allows achieving success in treatment even after proven inefficacy and intolerance of traditional immunosuppressants and TNF α antagonists.  Shown results testify to availability of a abatacept treatment of a refractory uveitis in patients with juvenile idiopathic rheumatoid arthritis and the necessity of further efficacy and tolerance research with protracted therapeutic schemes. Key words: children, juvenile idiopathic arthritis, uveitis, treatment, abatacept, lymphocyte co-stimulation blockade, biological treatment. (Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (5): 39–44.)